DETERMINANT OF REPUTATION RISK MANAGEMENT IN ISLAMIC BANKS IN INDONESIA - Chaerani Nisa; Nana Nawasiah (INQUISITIVE : International Journal of Economic, 2020)
This research aims to analyzes the determinant of reputation risk management in Islamic bank in Indonesia. We use content analysis method to examine whether there is reputation risk management in Islamic bank in Indonesia. It shows that, there is no relationship between those three variables in reputation risk management. There are other variables that more suitable with Indonesia case. As far as we know, this is the first research that focus on risk management measurement on syariah bank in Indonesia.